Socio-legal implications of cross-border marriage among Muslims in Malaysia : special reference to Malaysia, Thailand and Indonesia - Muhamad Helmi bin Md Said (Ahmad Ibrahim Kulliyyah of Laws, International islamic University Malaysia, 2017)
Marriage is a sacred bond, a tie between a man and a woman. Such relationship is blessed by Allah as it is mentioned in the Quran and the tradition (Sunnah) of the Prophet (pbuh). The laws created by man are meant to streamline the conduct of marriage, apart from the already provided hukm laid down in Islam. These laws are not intended to cause hardship to human life, rather they are meant to assist the humans in their conduct which would result into appreciation of this sacred institution of marriage. In order to ensure the process of marriage can be conducted and processed by the court, several pieces of legislation have been enacted. The law govern procedures for a marriage to be solemnized and registered with the intention to streamline the process and to ensure rights of both parties are protected. However, there are people who tend to violate these laws due to their own ignorance and this violation affects the future of such marriage and as well other people who are attached to it. This cross disciplinary socio-legal research study presents a unique perspective to the study on Muslims in Malaysia who are involved in cross-border marriage. This study focuses on cross-border marriage and its implication on socio-legal aspects in Malaysia. Cross-border marriage in Malaysia is commonly known as Kahwin Lari or runaway marriage. It has been defined as a marriage conducted by an unauthorised person, without permission of Registrar of Marriage in the States of Malaysia. The number of cross-border marriage is significantly high and it is overwhelming in almost every States in the Peninsular Malaysia. The study examines the socio-legal aspects of cross-border marriage in Malaysia by discussing its legality and procedures relating to it. Moreover, the study examines the social and legal impacts of cross-border marriage and its differences considering the attitudes and behaviour of the respondents. Taking into account regulatory policies and laws in recognising a valid marriage, this part of empirical research sought to identify and determine the differences of human attitude and behaviour towards cross-border marriage. This study employs qualitative and quantitative methods, and distribution of questionnaires to 400 respondents in four States in the Peninsular Malaysia. The data obtained were analysed by using descriptive and inferential statistics. For the descriptive statistics, the data in the form of percentages and frequencies have been used. Meanwhile, for inferential statistics; the T-Test, ONE-WAY ANOVA, Discriminant Analysis and Multiple Regression Analysis have been used to analyse the data. This study proves that even though there is a set of laws that governs the formalities and essentials of Muslim marriage, cross-border marriage continues to take place in the society and this is established by using demographic profiles of the respondents involved in this study. The study also shows that level of education plays a vital role in curbing this phenomenon and it also relates with the attitudes and behaviour of the respondents towards cross-border marriage. Finally, it concludes that there is a need to put a stop to the practice of cross-border marriage and it suggests alternative punishments in establishing an effective implementation and enforcement of the Islamic Family Laws in Malaysia.